SENSITIVITY STUDY ON ACID PROPERTIES AND RESERVOIR PERMEABILITY FOR ACIDIZING OPERATION AT CARBONATE RESERVOIR - Damora Siregar, Aldi
Decreasing well productivity is the issue of importance in the petroleum industry. One of the causes of this issue is formation damage represented by the skin effect. Fluid conductivity around the wellbore may significantly depressed because of the reduced initial permeability. Acidizing operation is one of the methods of reservoir stimulation to increase reservoir productivity. This study determines the optimum acidizing design by doing a sensitivity test. The optimum acidizing is happened when the skin value around the well is zero. If the skin value around the well is more than zero then the acidizing operation will be suboptimum. The suboptimum acidizing operation makes the well unable to achieve maximum production. The sensitivity test is done by evaluating the acid type, acid concentration, and reservoir permeability at the acidizing operation. The result of the sensitivity study shows that the strong type of acid with a higher concentration is the optimum type of acid for acidizing operation. The result also shows that the higher difference value of the initial reservoir permeability to the skin permeability, the higher acid volume and injection rate